Performance Measurement for Distributed Systems using 2TA and 3TA based on OPNET Principles - Ibrahim, Bishar R.; Zeebaree, Subhi R.M.; Hussan, Bzar Kh. (Science Journal of University of Zakho, 2019)
This paper presents a comparative study of two designs and analysis: Two Tier Architecture (2TA) and Three Tier Architecture (3TA). By using Optimized Network Engineering Tool (OPNET) modeler network-efficiency is done evaluation. OPNET, a professional simulation tool, is relied on to check the system with many clients from networks for both 2TA and 3TA. The outcomes demonstrate that 3TA is more capable than 2TA in term of data assessment is done utilizing OPNET modeler, which gives a convenient and easy-to-utilize platform for simulating extensive criterion networks. So, it will give more achievement when extended with many clients from networks with eight or sixteen clients. The models are utilized to study how the performance of the network is influenced by the different design decisions that are made to upgrade the system. This paper likewise examines ways in which the OPNET modules have been produced so that students could learn computer network concepts, and not exactly how to use OPNET software.